New style of honeycomb structures revealed on 3D seismic data indicate widespread diagenesis offshore Great South Basin, New Zealand - C. K. Morley (2018)
© 2017 In the Great South Basin, within the Eocene section, at time-depths around 700–900 ms two way time below the seafloor, unusual features are observed on 3D seismic data closely associated with polygonal faults. The features, referred to as honeycomb structures (HS), cover an area of ∼600 km2, are packed circular, oval, to polygonal depressions 150–400 m across in plan view and several to 10 + m in amplitude. Polygonal faults rapidly die out at the Marshall Paraconformity, which is overlain by the Oligocene Penrod Formation. Hence the polygonal faults are inferred to have formed prior to the Marshall Paraconformity, and they cross-cut HS features. Consequently the top of the HS probably formed at burial depths of around 375–500 m, which is their decompacted depth below the paraconformity. The interval containing HS is about 125 m vertical thick. There are several possible origins for the HS. The most probable is related to bulk contraction of the sediment volume accompanied by fluid expulsion, which suggests a diagenetic origin, in particular the opal-A/CT transition. There are actually two polygonal fault systems (PFS) present in the area. The Southern Tier 1 PFS lies laterally to the HS and overlaps with it. The Northern PFS (Tier 2) lies above the HS, appears to be independent of the HS, and formed in the upper 200–300 m of the sediment column. The Tier 1 PFS probably formed by shear failure related to the same diagenetic effects that caused the HS.